Reviewing and reframing the influence of relative age on ADHD diagnosis: beyond individual psycho(patho)logy. (2nd April 2020) - Koutsoklenis, Athanasios; Honkasilta, Juho; Brunila, Kristiina
ABSTRACT: Attention deficit hyperactivity disorder (ADHD) is a debated phenomenon and the link between schooling and the occurrence of ADHD diagnoses is worth critical scrutiny. This paper contributes to the academic debate by providing a literature review of the evidence on the influence of relative age effect (RAE) on being diagnosed with ADHD. Firstly, the review presents a general cross-national trend of a positive association between relative age and the probability of being diagnosed with ADHD compared with peers, thus showing that the younger-in-class children are more likely to be diagnosed with ADHD. Secondly, this paper outlines and presents discussion on the suggested explanations of the phenomenon as depicted in the literature reviewed. Finally, the paper proceeds to provide alternative frameworks for the explanation of the RAE on ADHD diagnosis that consider the broader social, cultural and political contexts in which the phenomenon takes place.